L'aria, il tempo dell'anima. Aerie potestates. Il simbolismo della vela e della conchiglia - Ilaria Sabbatini (I Quaderni del MAES, 2017)
The third book of the Codex Calixtinus, which is dedicated to the translation of Saint James' body in Compostela, ends with a brief chapter on Saint James' scallop shells and on their thaumaturgical power. According to the book, they can weaken the hail, the storms and the thunders and they can turn strong winds into light breezes. The scallop shells can control the air powers but, at the same time, according to both to the classical and the Christian philosophy of nature, they can sail as a boat using their valves as sails. This paper thus, following its symbolical meaning through the literary descriptions and the figurative representations, investigates the spiritual meaning of the pilgrimage in order to present a new interpretation of a practice which deeply influenced both the philosophical thought and the religious practice during the Middle Ages.